HOSPITALITAS GEREJA TERHADAP ANAK KORBAN PERCERAIAN - Astriani Ratu Langi; Wandrio Salewa (Institut Agama Kristen Negeri Manado, 2023)
Divorce is a situation where there is a brokedown in the relationship between husband and wife. The breakup of a relationship certainly triggers inner conflict, both between husband and wife and against children. In this study, the writer focuses on children as victims of divorce. This paper aims to formulate an offer of thought to the church regarding the church’s attitude towards the growth of faith in children of divorce victims as a form of church hospitality. This research uses qualitative methods with the tips research, it can contribute ideas in how the church should behave towards children who are victims of disorve and how the church expresses itself through service to them.